Clinicopathological changes and bacteriuria in pre- and post-relief of urethral obstruction in cats with lower urinary tract disease - Phoon, Melissa Hoi-Ee (2014)
Feline lower urinary tract disease (FLUTD) is an inflammatory condition involving the bladder and urethra of the cat. Although there are many possible causes of FLUTD, cats generally exhibit similar clinical signs of stranguria, dysuria, pollakiuria, and haematuria. Obstructive FLUTD is an emergency as it is potentially life-threatening and requires intensive monitoring during hospitalisation. Death most frequently occurs as a result of impaired renal function leading to failure of toxin removal and maintenance of adequate fluid and electrolyte balance in the body. The purpose of this prospective study was to determine assess the changes inelectrolytes, renal parameters, urinalysis, electrocardiogram, and the presence of bacteriuria in cats diagnosed with obstructive FLUTD in University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) from January to April 2014.Twenty hospitalised male cats presented with obstructive FLUTD and incompressible urinary bladders were recruited. The breeds included Domestic shorthair (n=1 0), Siamese (n= 1) and Persians (n=8) with the mean age of 36 months. Laboratory results (specifically renal parameters, urinalysis, urine culture), systolic blood pressure and electrocardiogram changes were obtained pre- and post-catheterisation. White blood cells count, urea, creatinine, potassium, and inorganic phosphate were significantly higher in obstructive FLUTD group compared to healthy group. No cats were found hypotensive in this study. Common finding in urinalysis were haematuria, leucocytes, and proteinuria. Interestingly, majority of the urine (n=13/17, 76%) was found no crystaluria.Triple phosphate (n=3/17, 18%) was the most common crystal in urinalysis. Urine bacteria culture revealed that 57% of urine samples collected on the first day of admission had no growth (n=8114). Bacteriuria was evident in 79.6% (n=11/14) of urine samples collected by day 3 post-catheterisation. The most common bacteria cultured were Escherichia coli and Kleibsella pneumoniae. 81% (n=13116) were hyperkalaemic (serum potassium> 5.5mmoI/L). There was significant relationship between serum potassium level and changes on electrocardiography (r= 0.75, P(l-tailed) <0.001). Statistically, the serum potassium level was significantly related to ventricular heart rate (r=> 0.40, P=0.015). From this study, catheterisation related urinary tract infection was evident. Despite electrolyte derangement, these obstructive FLUTD cats were not affected with hypotension. Future prospective studies that with a larger sample size and duration that includes urine bacterial culture and antibiotic sensitivity test is recommended.